Educational gaming for dental students: Design and assessment of a pilot endodontic‐themed escape game. (15th March 2020) - Aubeux, Davy; Blanchflower, Nuala; Bray, Estelle; Clouet, Roselyne; Remaud, Mathieu; Badran, Zahi; Prud'homme, Tony; Gaudin, Alexis
Abstract: Introduction: The concept of escape games dedicated to dental students is a new learning experience that has not yet been extensively explored. The aim of this pilot study was to assess the impact and perceived value of an endodontic‐themed escape game as assessed by fourth‐year dental students. Methods: This study was conducted at the University of Nantes,  Faculty of Dental Surgery using a cross‐sectional pre‐ and post‐test research design to assess students' changes in performance. Students in the fourth year of dental surgery study (n = 18) were divided in four groups for this study. The answers to the pre‐test/post‐test were 50 true/false questions. Moreover, a 20‐question perception survey was given to all the participants after completion of the escape game. The study data were collected in May 2019. An unpaired t test analysed the mean differences between the groups. Results: The results showed a statistically significant increase in post‐test results (75.33% ± 10.17% of correct answers) compared to the pre‐test results (67.33% ± 5.94% of correct answers) P  < .05. Analysis of variance revealed that this change in score was not significantly different between the four groups. The students perceived the endodontic‐themed escape game to be relevant. A one‐sample t test indicated that students' mean (SD) perception 4.4 (0.7) was statistically significantly higher than the mean value of the evaluation scale P  < .001. The students found this educational game to be a useful experience that helped them recall/apply knowledge whilst promoting teamwork. Conclusion: Therefore, this type of game can enhance students' learning and motivation.